Candida albicans translocation through the intestinal epithelial barrier is promoted by fungal zinc acquisition and limited by NFκB-mediated barrier protection. - Jakob L Sprague; Tim B Schille; Stefanie Allert; Verena Trümper; Adrian Lier; Peter Großmann; Emily L Priest; Antzela Tsavou; Gianni Panagiotou; Julian R Naglik; Duncan Wilson; Sascha Schäuble; et al. (PLoS Pathogens, 2024)
The opportunistic fungal pathogen Candida albicans thrives on human mucosal surfaces as a harmless commensal, but frequently causes infections under certain predisposing conditions. Translocation across the intestinal barrier into the bloodstream by intestine-colonizing C. albicans cells serves as the main source of disseminated candidiasis. However, the host and microbial mechanisms behind this process remain unclear. In this study we identified fungal and host factors specifically involved in infection of intestinal epithelial cells (IECs) using dual-RNA sequencing. Our data suggest that host-cell damage mediated by the peptide toxin candidalysin-encoding gene ECE1 facilitates fungal zinc acquisition. This in turn is crucial for the full virulence potential of C. albicans during infection. IECs in turn exhibit a filamentation- and damage-specific response to C. albicans infection, including NFκB, MAPK, and TNF signaling. NFκB activation by IECs limits candidalysin-mediated host-cell damage and mediates maintenance of the intestinal barrier and cell-cell junctions to further restrict fungal translocation. This is the first study to show that candidalysin-mediated damage is necessary for C. albicans nutrient acquisition during infection and to explain how IECs counteract damage and limit fungal translocation via NFκB-mediated maintenance of the intestinal barrier.